Social networks as a basis for interaction between authorities and non-profit organizations established on the basis of nationality in public communications space - V. V. Zotov; A. V. Gubanov (Цифровая социология, 2020)
The article is devoted to the discussion of the influence of modern information and telecommunication technologies on the process of building bilateral communication of state and municipal administration bodies with non-profit organizations created on the basis of national origin from the point of view of the management of public values and the stakeholder approach. The purpose of this article is to analyse the possibilities of organizing social and network interaction between the authorities and representatives of non-profit organizations as an institutionalized form of existence of national communities and faiths (on the example of social and network space of public communications of the Central Federal District). In the course of the study it was found that in the sphere of interethnic and interethnic relations the most relevant is the formation of a specialized single social and network resource in the information and communication space of the region. The preferred format of using such a resource, according to experts, should be related to the questions of obtaining information on decisions made by the authority and their subsequent discussion. At the same time, experts underestimate the possibilities of organizing dialogue and partnership on the basis of social media. At the same time, an analysis of existing social media practices has shown 1) a small proportion of accounts of state structures, which are responsible for interaction with representatives of national associations and diasporas; 2) the mismatch distribution in the social and network space of public communications pages of the authorities of the subject of the Russian Federation, carrying out in their activities interaction with national NGOs, accounts of non-profit organizations themselves, created on the basis of national origin, as well as representatives of national communities and diasporas. These circumstances allowed the authors to make a conclusion that it is necessary to establish in social networks systematic work of the authorities of the constituent entities of the Russian Federation with non-profit organizations, which represent national diasporas and communities on the territory of the regions of the Central Federal District.